Mineral allignment in a northern Wisconsin shear zone - Aslesen, Andrew; Costello, Bethany (My University, 2008)
Plate tectonics causes rocks to move and change shape, sometimes they change shape without breaking, forming structures called ductile shear zone. The exact reason why certain rocks form shear zones as opposed to others is not clearly understood at this time. The purpose of our research is to gain a better understanding of what causes these deformations in rocks. We are using an optical microscope and Geographic Information Systems (GIS) to analyze the mineral alignment of rocks within and around the shear zone exposed near the town of Mountain in Northeastern Wisconsin. These shear zones were formed between 1.8 and 2 billion years ago through plate collision. Most of these shear zones are now buried under glacial sediment, so the exposure of the Mountain Shear Zone provides a unique opportunity to study rock formations that are deformed deep underground. We are exploring the spatial distribution of mineral alignment around the shear zone. This could impact some further study on what may have caused the shear zone to form. Preliminary field work has been completed that includes field trips to the study area and collection of samples containing deformed and un-deformed granite. Thin sections will be made from the samples and further analyzed using computer software. Handheld GPS units were used take the locations where samples were taken. The locations will be plotted on top of a geologic map of the area using GIS in order to study to locations of deformed an un-deformed rocks in comparison the shear zone.
A poster containing visuals and text describing an undergraduate research project completed at the University of Wisconsin--Whitewater.
Keywords: Rock deformation -- Wisconsin; Shear zones (Geology) -- Wisconsin